2016
DOI: 10.1016/j.rse.2015.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Woody plant cover estimation in drylands from Earth Observation based seasonal metrics

Abstract: From in situ measured woody cover we develop a phenology driven model to estimate the canopy cover of woody species in the Sahelian drylands at 1 km scale. The model estimates the total canopy cover of all woody phanerophytes and the concept is based on the significant difference in phenophases of dryland trees, shrubs and bushes as compared to that of the herbaceous plants. Whereas annual herbaceous plants are only green during the rainy season and senescence occurs shortly after flowering towards the last ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 51 publications
5
87
0
Order By: Relevance
“…Herrmann and Tappan (2013) found a reduction of woody species richness and a shift to more xeric species since the early 1980s, as well as an increasing dominance of shrubs in central Senegal. Other studies from Senegal and Mali confirmed these results (Maranz, 2009;Miehe et al, 2010;Herrmann and Tappan, 2013;Brandt et al, 2014bBrandt et al, , 2015Brandt et al, , 2016aSpiekermann et al, 2015). Kaptué et al (2015) refer to a post-drought tree population recovery and present evidence of a decline in populations of economically and culturally important trees and shrubs despite the increase in woody cover.…”
Section: Contributions Of Other Authorsmentioning
confidence: 58%
See 2 more Smart Citations
“…Herrmann and Tappan (2013) found a reduction of woody species richness and a shift to more xeric species since the early 1980s, as well as an increasing dominance of shrubs in central Senegal. Other studies from Senegal and Mali confirmed these results (Maranz, 2009;Miehe et al, 2010;Herrmann and Tappan, 2013;Brandt et al, 2014bBrandt et al, , 2015Brandt et al, , 2016aSpiekermann et al, 2015). Kaptué et al (2015) refer to a post-drought tree population recovery and present evidence of a decline in populations of economically and culturally important trees and shrubs despite the increase in woody cover.…”
Section: Contributions Of Other Authorsmentioning
confidence: 58%
“…Since the millennium, additional data like MODIS and SPOT-Vegetation (VGT) NDVI data have been used (e.g. Herrmann and Tappan, 2013;Dardel et al, 2014a;Brandt et al, 2015Brandt et al, , 2016aBrandt et al, , b, 2017aTong et al, 2017). Reviews are provided by Higginbottom and Symeonakis (2014), Knauer et al (2014), and Mbow et al (2014.…”
Section: Contributions Of Other Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A diverse set of analytical methods that exploit phenological information in time-series of multispectral images has been developed for distinguishing and mapping vegetation cover types [20][21][22][23][24][25], estimating and mapping biomass and vegetation fuel loads [26][27][28][29][30] and for investigating how vegetation and related ecosystem processes respond to management, disturbance, weather, drought and climate change [31][32][33][34][35][36][37]. These methods examine the seasonal growth dynamics of the vegetation through quantification and analysis of various metrics of the time signal observed within one or more years.…”
Section: Multispectral Image-based Approaches To Mapping Of Semiarid mentioning
confidence: 99%
“…Gessner et al [55] applied decision tree regression to a set of satellite-derived phenology metrics for the wet and dry season to estimate fractional cover of woody, herbaceous and bare soil in savanna regions of southern Africa. Brandt et al [25] estimated and mapped woody plant cover in the Sehelian drylands of Africa by using multiple regression modeling of the relationships between various satellite-derived phenological metrics and field data.…”
Section: Multispectral Image-based Approaches To Mapping Of Semiarid mentioning
confidence: 99%